Role of "Lead Market" factors in globalization of innovation: Emerging evidence from India & its implications - Rajnish Tiwari; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2011)
Access to lead markets is generally regarded as an important driver of the increasing globalization of innovation since these are considered to be early indicators for emerging customer needs. They are traditionally thought to exist in economies with high per capita income, sophisticated markets and high international visibility. We, however, propose that there is an increasing evidence of lead market tendencies in some emerging economies, e.g. India. We undertake a literature review to crystallize the need for an update/extension of the existing model to better reflect the changed ground realities and propose that factors such as voluminous markets, strong technological capabilities, and favorable government policies may be able to offset some of the disadvantages rooted in traditional deficiencies of developing economies. Engaging a developing country lead market may be useful for firms in securing better access to markets at the bottom of the economic pyramid, worldwide.
urn:nbn:de:gbv:830-tubdok-11088
Keywords: 650; Lead Markets; India; Globalization of Innovation; Internationalization of R&D; Frugal Innovations